Internalizing Environmental Care Values Through Waste Management: Impacts on Elementary Students' Social Relations - Ahmad Fauzi Pulungan; Rahmi Seri Hanida; Hamda Hamidah; Nuratikah (cendekia citra gemilang, 2026)
Environmental issues, particularly waste management, have emerged as one of the most pressing challenges in sustainable development globally. This study analyses the process of internalizing environmental care values through waste management and its impact on the social relations of students at SDN 154 Aek Ngali. A qualitative case study design was employed, and data were collected through participatory observation, in-depth interviews, and documentation. The findings demonstrate that the internalization of environmental care values proceeds through four interconnected mechanisms: habituation, teacher modeling, positive reinforcement, and social collaboration. Daily class duty schedules and routine communal cleaning activities not only build students' ecological consciousness but also strengthen cooperation, solidarity, and interpersonal communication and reduce interpersonal conflict among students. Waste management in schools thus functions as an integrative socio-ecological educational medium where ecological awareness formation proceeds hand in hand with the strengthening of social relations. This study contributes theoretically to environmental-based education by emphasizing the social dimension as a critical outcome of ecological practices at the elementary school level and provides a practical basis for developing waste management programs oriented not only toward environmental cleanliness but also toward the formation of a collaborative and sustainable social culture.